Nitrogen : Understanding the elements of the periodic table - Hasan, Heather (New York : The Rosen Publishing Group, 2005)
Explain the characteristics of nitrogen, where it is found, how it is used by humans, and its relationship to other elements found in the periodic table.
includes bibliographical references and index.
Keywords: Nitrogen -- Juvenile literature